2017
DOI: 10.1002/sim.7554
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for analysis of time‐to‐event outcomes measured with error: Bias and correction with SIMEX

Abstract: For time-to-event outcomes, a rich literature exists on the bias introduced by covariate measurement error in regression models, such as the Cox model, and methods of analysis to address this bias. By comparison, less attention has been given to understanding the impact or addressing errors in the failure time outcome. For many diseases, the timing of an event of interest (such as progression-free survival or time to AIDS progression) can be difficult to assess or reliant on self-report and therefore prone to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…In fact, some forms of error in the outcome will bias the proportional hazards parameter but not the acceleration parameter. 27 The generalized raking estimators are consistent whenever the design-weighted complete case estimating equations (eg, HT estimator) yields consistent estimators; they use influence functions based on the unvalidated data as auxiliary variables to improve efficiency over the complete case estimator and can be used under outcome-dependent sampling. The raking estimators are not sensitive to the measurement error structure, which is in contrast to the RC and RSRC estimators that can perform poorly when the error structure is not correctly specified.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some forms of error in the outcome will bias the proportional hazards parameter but not the acceleration parameter. 27 The generalized raking estimators are consistent whenever the design-weighted complete case estimating equations (eg, HT estimator) yields consistent estimators; they use influence functions based on the unvalidated data as auxiliary variables to improve efficiency over the complete case estimator and can be used under outcome-dependent sampling. The raking estimators are not sensitive to the measurement error structure, which is in contrast to the RC and RSRC estimators that can perform poorly when the error structure is not correctly specified.…”
Section: Discussionmentioning
confidence: 99%
“…However, this bias has been shown to be small when differences between groups are moderate in terms of hazard ratios (Oh et al. 2018 ). Furthermore, in some situations in which bias was found to be substantial, bias attenuates observed differences between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Covariate measurement error, particularly classical measurement error or extensions of it, has been well studied in the literature, and methods to correct the bias resulting from such error have been well developed (Carroll et al., 2006). Although less attention has been given to errors in an outcome of interest, there has been some recent work looking at errors in binary outcomes (Magder & Hughes, 1997; Edwards et al., 2013; Wang et al., 2016), discrete time‐to‐event outcomes (Hunsberger et al., 2010; Magaret, 2008; Meier et al., 2003), and to a lesser extent, continuous time‐to‐event outcomes (Gravel et al., 2018; Oh et al., 2018). There has been even less work to understand the impact of errors in both covariates and a time‐to‐event outcome, but it has recently been shown that ignoring such errors can cause severe bias in estimates of effects of interest (Boe et al., 2020; Giganti et al., 2020; Oh et al., 2019).…”
Section: Introductionmentioning
confidence: 99%